Transitioning from pediatric to adult multiple sclerosis care: Challenges, strategies and therapy - Beniwal, Shreya Singh (2025)
Multiple sclerosis (MS) is a chronic autoimmune condition causing damage to the protective covering of nerves in the central nervous system. Pediatric multiple sclerosis is a rare form of the disease that affects 3-5% of individuals with multiple sclerosis. Pediatric Onset Multiple Sclerosis (POMS) has a rather different clinical profile from the more prevalent adult multiple sclerosis. Alongside the classic symptoms of multiple sclerosis, children tend to present with various atypical symptoms that can impact motor milestones, speech development, and cognitive functions. This review aims to explore the pathogenesis, clinical features, diagnosis and progression of Pediatric Onset Multiple Sclerosis into adulthood, address the challenges accompanying this transition and identify strategies and therapies to overcome them. Pediatric multiple sclerosis patients transitioning into adulthood face many challenges, such as difficulty in school and social life, and dealing with uncertainties especially due to changes in healthcare providers from pediatric to adult settings. These challenges can be overcome by an emphasis on a well-structured transition plan, early planning, personalized care, proper counselling of the patient as well as the family and caretakers, a multidisciplinary approach with good communication and coordination between all healthcare personnel a robust support network with a gradual transition rather than an abrupt one. Proper care during the transition period is crucial to enhance patient adherence and deepen the understanding of the disease for both patients and their families. This will empower them to seek timely assistance when needed, reduce loss to follow-up, and ultimately improve overall quality of life.